Pomiar kapitału intelektualnego w przedsiębiorstwie – aspekty metodyczne - Skrzypek, Elżbieta (Wydawnictwo Naukowe UAM, 2014)
In the new economy, efficient knowledge-based resource management of intangible assets can be an important source of a company’s market success. Increasingly, it is being noted that there are differences between the book value and market value of assets. The value of intellectual capital is the source of this difference. The aim of this article is to analyze the methods of measuring intellectual capital in a company and point out that the measurement of intellectual capital is an important element of the management process. It is becoming necessary to measure intellectual capital because its role as a factor in a company’s success is growing. This measurement is done at the macroeconomic (KAM, KEI, KI) and microeconomic levels (BSC, Scandia Navigator, IC Rating and Intangible Assets Monitor). A system of indicators, both quantitative and qualitative ones, is used to measure intellectual capital on enterprise level in order to show the level of and changes in its components. The methods of measuring intellectual capital should be chosen based on their capacity to increase a given company’s potential. The analyses that were carried out for the purpose of this article are theoretical in character and are based on the existing scientific literature as well as the author’s own reflections.
Measurement of Intellectual Capital in an Enterprise: Methodological Aspects
Keywords: intellectual capital; intangible assets; measuring intellectual; capital; intellectual capital measurement methods